C.29C>T polymorphism in the transforming growth factor-β1 (TGFB1) gene correlates with increased risk of urinary bladder cancer. Issue 2 (October 2015) - Gautam, Kirti Amresh; Pooja, Singh; Sankhwar, Satya Narayan; Sankhwar, Pushp Lata; Goel, Apul; Rajender, Singh
Highlights c.29C>T in the TGFB1 gene correlates with increased risk of bladder cancer. c.29C>T increases the risk significantly in the recessive form. c.74G>C and +140A>G in the TGFB1 gene do not correlate with bladder cancer risk. Smokers with c.29C>T showed a stronger correlation with bladder cancer.